Associations of reverse triiodothyronine serum levels with anxiety, depression, and health related quality of life after experiencing acute ischemic stroke - Saulius Taroza; Helene Plamondon; Aurelija Podlipskyte; Nijole Kazukauskiene; Nicolas Francisco Narvaez Linares; Marilou Poitras; Julius Burkauskas; Narseta Mickuviene (Frontiers in Neurology)
AimThis study intended to explore associations of reverse triiodothyronine (rT3) with emotional disturbances and health-related quality of life (HRQoL) after experiencing acute ischemic stroke (AIS).Materials and methodsSerum samples from individuals with AIS were collected on admission to three Lithuania stroke centers and investigated for free tetraiodothyronine, free triiodothyronine (fT3), rT3, and thyroid stimulating hormone levels. At discharge, emotional disturbance was evaluated using the Hospital Depression and Anxiety Scale (HADS), and HRQoL using the EQ-5D-5L scale.ResultsAnalyses included 159 individuals (59.7% male and 40.3% female; mean (SD) aged 66.4 [10.3] years), 52.83% of which showed increased rT3 levels upon admission. After adjustment for age, sex, National Institutes of Health Stroke Scale scores, previous stroke, modified Rankin Scale before AIS ≤ 2, and diabetes mellitus, multivariable linear regression revealed negative associations of rT3 with HADS total score (β = −0.163; p = 0.046) and HADS-D subscale score (β = −0.187; p = 0.019). Analyses supported a positive relationship between the fT3 ratio to rT3 with HADS-D score (β = 0.157; p = 0.046) and rT3, rT3 × fT3 product with EQ-5D index score (β = 0.157; p = 0.044 and β = 0.179; p = 0.023, respectively).ConclusionWe found that individuals who experienced AIS and had higher levels of rT3 at hospital admission had less emotional disturbance and better HRQoL when discharged.